12p+19q+p-6q-3p=

Simple and best practice solution for 12p+19q+p-6q-3p= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12p+19q+p-6q-3p= equation:


Simplifying
12p + 19q + p + -6q + -3p = 0

Reorder the terms:
12p + p + -3p + 19q + -6q = 0

Combine like terms: 12p + p = 13p
13p + -3p + 19q + -6q = 0

Combine like terms: 13p + -3p = 10p
10p + 19q + -6q = 0

Combine like terms: 19q + -6q = 13q
10p + 13q = 0

Solving
10p + 13q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-13q' to each side of the equation.
10p + 13q + -13q = 0 + -13q

Combine like terms: 13q + -13q = 0
10p + 0 = 0 + -13q
10p = 0 + -13q
Remove the zero:
10p = -13q

Divide each side by '10'.
p = -1.3q

Simplifying
p = -1.3q

See similar equations:

| 1+x+2=3+x+4 | | 4(x+2)=30+3x | | X^2lnx-4lnx=0 | | 6a=80-4d | | 8x+10=8x-9 | | X^2=220+5 | | x^2+5x-3=3x+5 | | x^2+16x-15=0 | | 17=(-13)-(8x) | | 21-15=3(x-7) | | 15a+14b+6c+5c-5b-5a= | | 2x+7y+z=29 | | 4x-2(x-3)=-2+5x-4 | | 6x-3x=7 | | 50=47+12+4w | | -5(x)+23=-7 | | 3x+2y+z=17 | | 6r+2(r+6)=4r+12 | | 12+4x=-2x-9 | | 3y+8x+3=14+8x | | x^2-6x+4=-9x+2 | | 3=0.5+11 | | 2x+5+110= | | 2x+4=2x+2(x+2) | | x^2-8x-5=4 | | 9n-15-16n=13 | | -5u-16=2(u-1) | | 5(X-2)=11 | | 3x+y+2z=13 | | 300x^2-300x+50=0 | | -8(r-8)=-32 | | 4x+y+5z=24 |

Equations solver categories